A study of surgical profile of patients undergoing hemorrhoidectomy - Pande, Pradeep Kumar; Dhruv, Yashwant (International Surgery Journal, 2017)
Background: Hemorrhoids are common. It is usually defined as increase in size as well as distal displacement of apparently normal cushions which generally leads to symptoms. Globally many people are affected. It is considered as a major public health problem. It has a multifactorial etiology. Objective was to surgical profile of patients undergoing hemorrhoidectomy. Methods: Present hospital based cross sectional study was carried out for a period of one and a half years at department of general surgery, Gandhi medical college and associated Hamidia hospital, Bhopal, Madhya Pradesh, India, among 90 patients undergoing hemorrhoidectomy. Thorough history, detailed clinical examination, complete rectal examination and hemoglobin estimation was carried out. Results: It was found that maximum cases were below the age of 40 years. Males suffered more (73.3%) than females (26.7%). Hemorrhoids were seen commonly among urban dwellers (87.7%) than rural dwellers (12.3%). The most common presenting complaint was bleeding in 97.7% of cases. Maximum patients reported to the hospital within one-year history of bleeding i.e. 71.1%. Majority i.e. 73.3% had normal hemoglobin levels. 46.6% had ano-rectal disease. Conclusions: Incidence of hemorrhoids was more common among the cases of the present study. People below 40 years of age were commonly affected. It was more in males. Bleeding was the most common presenting symptom. Anemia was not so common. Anal fissure was the commonest associated co-morbidity.